Immune mediation between sarcopenia, performance status, and survival in gastric cancer patients undergoing radical resection - Diao, Pei; Wang, Yan; Wang, Xin; He, Lijuan (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to explore the combined impact of sarcopenia and physical performance on immune status and prognosis in patients with resectable gastric cancer, and to evaluate the mediating role of immune function.MethodsA retrospective cohort of 413 patients undergoing radical gastrectomy was analyzed. Sarcopenia was assessed by skeletal muscle index (SMI) on CT, and physical performance by ECOG score. Patients were stratified into ISPS (Integrated Sarcopenia and Performance Status) high, medium, and low groups. Peripheral lymphocyte subsets were measured preoperatively. Kaplan–Meier curves, Cox regression, and mediation analysis were used to examine survival and immune interactions. Prognostic nomograms were constructed based on independent variables.ResultsLower ISPS scores were significantly associated with reduced CD3+, CD8+, and NK cells. Survival analysis showed that the ISPS-Low group had significantly worse progression-free survival (PFS, χ² = 27.36, P < 0.001) and overall survival (OS, χ² = 31.54, P < 0.001). ISPS and CD8+ T cell levels were independent predictors of both PFS and OS. Mediation analysis indicated that CD8+ T cells partially mediated the effect of ISPS on survival, accounting for approximately 24% of the total effect. Nomograms incorporating ISPS, immune status, TNM stage, and tumor size demonstrated good predictive performance (C-index: 0.732 for PFS, 0.718 for OS).ConclusionSarcopenia and poor functional status are linked to impaired immunity and unfavorable outcomes in gastric cancer. Immune status may partially explain this relationship. ISPS may serve as a useful prognostic tool, and integrating physical and immune assessments could improve prognostic evaluation and support personalized perioperative strategies.